Institutional Arrangements and Government Audit Independence in China. (12th August 2016) - Xiao, Jason Zezhong; Yang, Suchang; Zhang, Xinmin; Firth, Michael
Abstract : China has adopted an executive‐dominated government audit system (GAS), which is frequently criticized for lacking independence. Through a questionnaire survey and interviews, we investigate whether and how the reporting/control requirements of the GAS (hereafter, the institutional arrangements) result in a lack of government audit independence in China and how this affects budget supervision by the People's Congress. We contribute field evidence to support the prediction that an executive‐dominated GAS lacks independence and transparency, which in turn is detrimental to the wider accountability regime. However, the specific level of independence varies according to the types and levels of government audit. Our findings enrich the government audit literature, enhance our understanding of the relationship between institutional arrangements and audit independence in a transition economy, and serve as a call for institutional reform relating to the Chinese GAS.